Endoscopic Resection of a Giant Pedunculated Leiomyoma of the Sigmoid Colon - Andrisani, Gianluca; Pizzicannella, Margherita; Taffon, Chiara; Di Matteo, Francesco Maria (Journal of Digestive Endoscopy, 2017)
The leiomyoma is a benign smooth muscle tumor and may occur throughout the entire digestive tract, more frequently in the stomach, and small intestine, but is rarely seen in large bowel. Furthermore, a colonic giant pedunculated leiomyoma is very rare. The traditional management option for a colonic leiomyoma is surgical resection. However, the endoloop‑assisted polypectomy could be the treatment of choice even for very large lesions.
Keywords: Colonscopy; endoscopic therapy; pedunculated leiomyoma